Simmel and Social Interaction: An Ethnomethodological Perspective - Liberman, Kenneth (Simmel Studies, 2025)
The most fruitful use of Simmel’s seminal notion of Wechselwirkung may be the way he applied it to explain the generation of social formations that continuously facilitate interaction in society. Objective forms are necessary for people to share a life together, to think clearly, and to help them render their lives orderly; however, these forms necessarily become alien to those who develop them. Simmel sought to establish sociological inquiries that were based solidly upon a clear grasp of the dynamic and interconnected nature of life and that avoid reifying the phenomena they study. Ethnomethodology, with its attention to the ongoing, contingent details that compose ordinary life has followed a similar aim